IRF4 Mediates Immune Evasion to Facilitate EBV Transformation - Ling Wang; Culton R. Hensley; Jahan Rifat; Adam D. Walker; Katharine Ning; Jonathan P. Moorman; Zhi Q. Yao; Shunbin Ning (Viruses, 2025)
The lymphocyte-specific transcription factor interferon regulatory factor 4 (IRF4) is a key player in immune evasion in cancers, with the complex mechanism(s) being barely understood. In this study, we have focused on the role of IRF4 in regulating T cell functions through its transcriptional regulation of programmed death 1 (PD1) and its ligand PD1 ligand 1 (PD-L1), which were identified as IRF4 transcriptional targets in multi-omics analysis. We have shown that IRF4 transcriptionally regulates both PD1 and PD-L1, promoting immune suppression in the context of Epstein–Barr virus (EBV) infection. Co-culturing EBV+ JiJoye lymphoma cells with CD4+ T cells or with peripheral blood mononuclear cells (PBMCs) downregulates CD4+ T cell functions, but the depletion of IRF4 in EBV+ JiJoye lymphoma cells reduces PD1 and PD-L1 expression, and partially restores CD4+ T cell functions. Moreover, CD4+ T cell depletion from PBMCs enhances EBV transformation, and EBV has a greater efficiency in transforming PBMCs from HIV patients with impaired CD4+ T cell functions. These findings support the role of IRF4 in immune evasion by upregulating PD1/PD-L1 during EBV transformation, and that functional CD4+ T cells are essential for limiting EBV transformation.